Challenges and Prospects of State Administrative Law for Enforcing Consumer Rights in the Digital Era - Laksono, Farmasinta Setyaning; Subekti, Rahayu; Hermawan, Sapto (CV. Strata Persada Academia, 2025)
The digital era has significantly transformed consumer behavior while simultaneously presenting new challenges in the protection of consumer rights. This study aims to analyze the juridical challenges and prospects of state administrative law in enforcing consumer rights within the digital context. Employing normative legal research methods, this study is based on secondary data, including statutory regulations, academic literature, and tertiary legal references. The findings reveal a regulatory gap caused by the rapid pace of technological advancement, weak inter-agency coordination, limited digital literacy among consumers, and the complexity of cross-border transactions. Although the Consumer Protection Law serves as the primary legal foundation, its implementation remains insufficient in the digital realm. Consequently, state administrative law must undergo adaptive transformation by enhancing digital public services, personal data protection, and the accountability of public officials. Comprehensive regulatory reform, capacity building for legal apparatus, development of digital infrastructure, and public education are essential to establishing an effective and responsive consumer protection framework in the digital age. This research contributes both theoretically and practically to the renewal of administrative law and the formulation of adaptive public policy for digital consumer protection.